Therapeutic efficacy and safety of initial triple combination of metformin, sitagliptin, and lobeglitazone in drug-naïve patients with type 2 diabetes: initial triple study. Issue 1 (14th January 2020) - Lim, Soo; Ku, Eu Jeong; Lee, Seo Young; Lee, Ji Hyun; Lee, Jie-Eun; Kim, Kyoung Min; Davies, Melanie J
Abstract : Objective: To compare the efficacy and safety of an initial triple therapy using metformin, a dipeptidyl peptidase-4 (DPP4) inhibitor, and thiazolidinedione with a stepwise approach using sulfonylurea and metformin in new-onset, drug-naïve patients with type 2 diabetes. Research design and methods: Among drug-naïve patients with 9.0%–12.0% glycated hemoglobin (HbA1c) but no hyperglycemic symptoms, 100 subjects who started triple medications (metformin 1000 mg/day, sitagliptin 100 mg/day, and lobeglitazone 0.5 mg/day) were selected as an initial triple therapy group. Age and body mass index-matched subjects (n=100) who started glimepiride (≥2 mg/day with uptitration) and metformin (≥1000 mg/day with uptitration) were selected as a conventional therapy group. We investigated changes in HbA1c level, dynamic indexes for insulin sensitivity and β-cell function, and hypoglycemia. Results: After 12 months of treatment, HbA1c levels decreased significantly in both groups: from 10.7%±1.0% to 6.7%±1.3% in the triple group, and from 10.5%±1.0% to 7.3%±1.2% in the conventional therapy group. At 12 months, achievement of the HbA1c target (<7.0%) was higher in the triple group than in the conventional group (70% vs 52%, p<0.01). Dynamic indexes related to β-cell function and insulin sensitivity improved, and albuminuria reduced significantly only in the triple group. Hypoglycemia was more common in the conventional group. Conclusions: Initial triple combination therapy with the DPP4 inhibitor, metformin, and thiazolidinedione showed a higher achievement of the target HbA1c goal with a lower risk of hypoglycemia, better restoration of β-cell function, and multiple metabolic benefits, implying durable glycemic control. This strategy may be useful for patients presenting with type 2 diabetes and high HbA1c levels.